The I-search paper - Macrorie, Ken (Boynton/Cook Publishers, Heinemann, 1988)
Book shows students what authority is in matters of learning and invites them to join the author and teacher in the educational movement called "Writing to Learn". To put this book in the hands of all the students in the course is not only to help them carry out an I-Search but to introduce them in a delightful way to the resources and tools of intellectual inquiry -- but one that never forgets the emotional or physical side of human activity